"How great a good was Luria’s having lived": Promoting the Moor of Sicily in Robert Brwoning’s Luria (1846) - El idrissi, Zakariae (International Journal of Language and Literary Studies, 2023)
In an attempt to find a possible alternative to imperial orientalism, this essay brings to the forefront Robert Browning’s Luria: A Tragedy (1846) as a case study exemplifying irregularity, volatility, and discontinuity in Western discursivity. Drawing upon critics such as Dennis Porter, Kathryn Tidreck, John Mackenzie, Robert Irwin, and Ali Behdad, who take history, context, the author’s experience, and socio-cultural particularities as factors defining the heterogeneity of orientalism, I argue that Luria sharply deviates from hegemonic orientalism in a way that perfectly fits with Browning’s mysticism and disengagement from politics. Away from stereotypical dogmatism, the play promotes its Moor on stage both militarily and morally and employs diverse strategies to delegitimize racial antagonism and refute clichéd statements about the Moor.